Events and Controversies: Influences of a Shocking News Event on Information Seeking - Koutra, Danai; Bennett, Paul; Horvitz, Eric (Proceedings of the 24th Annual International World Wide Web Conference (WWW '15) (This paper revises and extends work in TAIA Workshop at SIGIR 2014 and arXiv:1405.1486.), 2015)
It has been suggested that online search and retrieval contributes to the intellectual isolation of users within their preexisting ideologies, where people’s prior views are strengthened and alternative viewpoints are infrequently encountered. This so-called “filter bubble” phenomenon has been called out as especially detrimental when it comes to dialog among people on controversial, emotionally charged topics, such as the labeling of genetically modified food, the right to bear arms, the death penalty, and online privacy. We seek to identify and study information-seeking behavior and access to alternative versus reinforcing viewpoints following shocking, emotional, and large-scale news events. We choose for a case study to analyze search and browsing on gun control/rights, a strongly polarizing topic for both citizens and leaders of the United States. We study the period of time preceding and following a mass shooting to understand how its occurrence, follow-on discussions, and debate may have been linked to changes in the patterns of searching and browsing. We employ information-theoretic measures to quantify the diversity of Web domains of interest to users and understand the browsing patterns of users. We use these measures to characterize the influence of news events on these web search and browsing patterns.